The Emergence and Development of Ethnic Strongholds and Frontiers of Collective Violence in Jos, Nigeria. (December 2019) - Madueke, Kingsley L.
Abstract: Contestations over indigene rights and political representation resulted in Christian-Muslim riots in the Nigerian city of Jos where, between 2001 and 2010, over 5, 000 people were killed. This study complements existing literature on the spatial dimension of violence by focusing on how Jos's neighborhoods were transformed from everyday residential areas to spaces of ethnic differentiation and violence. It employs an ethnographic study to map the emergence and development of ethnic strongholds and frontiers, two kinds of socio-spatial settings conceptualized to help explain the spread and patterns of violence across Jos's neighborhoods. Résumé: Les contestations sur les droits des peuples autochtones et leur représentation politique ont entraîné des émeutes entre chrétiens et musulmans dans la ville de Jos, Niger, où entre 2001 et 2010, plus de 5 000 personnes ont été tuées. Cette étude complète la littérature existante sur la dimension spatiale de la violence en mettant l'accent sur la transformation des quartiers de Jos, zones résidentielles de vie quotidienne, en espaces de différenciation ethnique et de violence. Cet article utilise une étude ethnographique pour cartographier l'émergence et le développement de bastions ethniques et de frontières, deux genres de cadres socio-spatiaux conçus pour expliquer les différents scénarios de la violence et leurs propagations dans les quartiers de Jos. Resumo: Os protestos em defesa dos direitos e da representação política dos povos indígenas resultaram em revoltas cristãs e muçulmanas na cidade nigeriana de Jos, onde, entre 2001 e 2010, foram assassinadas mais de cinco mil pessoas. O presente estudo vem complementar a literatura disponível sobre a dimensão espacial da violência, centrando-se no modo como os bairros de Jos, outrora zonas residenciais, se transformaram em espaços de diferenciação étnica e de violência. Partindo de um estudo etnográfico, cartografa-se aqui e a emergência e o desenvolvimento de fronteiras e bastiões étnicos, dois tipos de enquadramento socioespacial que foram concebidos como ferramentas para ajudar a explicar a disseminação e os padrões de violência nos bairros de Jos.